1992
DOI: 10.1099/00222615-37-2-109
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of methods for typing coagulase-negative staphylococci

Abstract: Summary.One hundred and forty-two coagulase-negative staphylococci (CNS) isolated from dialysate effluent or skin of patients receiving continuous ambulatory peritoneal dialysis (CAPD) were typed by extended antibiogram (16 antibiotics) and biotype (26 reactions). These isolates were then typed by supplementary methods to determine the most suitable typing method for an epidemiological study of antibiotic resistance. These included phage typing, reverse phage typing, plasmid typing, whole-cell protein typing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1993
1993
1999
1999

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…SDS-PAGE with Coomassie staining has produced distinct banding patterns for Staphylococcus species (Clink & Pennington, 1987). Dryden et al (1992) found that SDS-PAGE has a higher discriminatory power than globulin. Cultures grown in brain-heart infusion at 37 "C for 18 h are centrifuged and washed in 1/15 M phosphate buffer (pH 5.9).…”
Section: Total Protein Profilesmentioning
confidence: 99%
“…SDS-PAGE with Coomassie staining has produced distinct banding patterns for Staphylococcus species (Clink & Pennington, 1987). Dryden et al (1992) found that SDS-PAGE has a higher discriminatory power than globulin. Cultures grown in brain-heart infusion at 37 "C for 18 h are centrifuged and washed in 1/15 M phosphate buffer (pH 5.9).…”
Section: Total Protein Profilesmentioning
confidence: 99%
“…Intendente Jorge Palacios, 30003 Murcia, Spain. and plasmid profiles analyses (5). The only practical first-line methods to identify isolates of CNS in the routine laboratory, however, are the use of biotype profiles and antibiograms.…”
mentioning
confidence: 99%
“…A humoral response to CNS in serum and dialysate in CAPD patients has been detected by enzyme immunoassay, and CNS peritonitis has been shown to provoke a rise in antibody levels in some patients (13). Western immunoblotting, which we have adapted to type CNS (14), is a highly sensitive technique which may be employed to detect an antibody response to specific antigens. Immunoblotting has been employed to diagnose enterococcal endocarditis (15), and to investigate the antibody response of serum from healthy volunteers to Staphylococcus aureus (16).…”
Section: Serological Response To Coagulase-negative Staphylococci In mentioning
confidence: 99%
“…Immunoblotting was carried out as described previously (14). Briefly, whole cell protein of the staphylococcal strains, extracted by sonication, was separated by SDS-PAGE in 10 % polyacrylamide gel in a discontinuous buffer system at 10*C. After transfer of the separated staphylococcal protein to the nitrocellulose membrane (0.45 ~tm membrane pore, Schleicher & Schuell, Germany) using 100 mA current for 15 h and blocking the free protein sites on the membrane with 5 % bovine serum albumin (BSA) in Tris buffered saline, the membranes were cut into pairs of lanes.…”
Section: Patients and Samplesmentioning
confidence: 99%